EFEKTIVITAS PENERIMAAN PBJT MAKANAN DAN/ATAU MINUMAN PADA Q-MALL BANJARBARU SERTA KONTRIBUSINYA TERHADAP PENERIMAAN PAJAK DAERAH DI KOTA BANJARBARU - Nur Indah Sari; Doni Stiadi (Universitas Lambung Mangkurat, 2025)
This study is intended to determine the effectiveness of the revenue in the Food and/or Beverage PBJT at Q-Mall Banjarbaru, as well as to find out the amount of contribution of the Food and/or Beverage PBJT at Q-Mall Banjarbaru to the revenue of PBJT in Banjarbaru City and to determine the amount of contribution of PBJT Food and/or Beverage at Q-Mall Banjarbaru to regional tax revenue in Banjarbaru City. This study uses a quantitative descriptive method that uses secondary data, the data collection technique used is documentation. The results of this study show that from 2021 to 2024 the effectiveness of the Food and/or Beverage PBJT is classified as a very effective criterion, while the overall contribution of the Food and/or Beverage PBJT is classified as a sufficient contributing criterion.